Analisis Implementasi Peran Sumberdaya Manusia Sebagai Mitra Strategik, Ahli Administratif,Employee Champion, dan Agen Perubahan: Studi pada Top Companies di Indonesia - Siti Fatimah Nurhayati (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2001)
The change and increasingly complex business environment has forced many companies to make radical organizational transformation. Facing with this new challenge, the organization should develop their competitive advantage on the basis of organizational capabilities and the execution of new roles of human resource. This research analyzes the execution of the human resource roles at top companies in Indonesia. The result shows that generally top companies in Indonesia have executed four types of human resource roles (strategic partner, administrative expert, employee champion and the change agent role), nevertheless the execution pattern of human resource roles are different. The execution of one role will support the execution of other role.Keywords: The change and increasingly complex business environment, radical organizational transformation, the new roles of human resource.